IMPLEMENTASI CHATBOT YANG TERINTEGRASI LAYANAN KEPOLISIAN DALAM PEMBUATAN SIM - Allaam, Ekananda Naufal; Zuliarso, Eri (ITP Press, 2024)
This research explores the deployment of a chatbot integrated with police services, focusing on the driver's license (SIM) application process. The urgency of this research arises from the need to enhance the accessibility and efficiency of public services. By leveraging Natural Language Processing (NLP), the chatbot is designed to provide rapid and accurate information regarding the SIM application procedures, renewal guidelines, and necessary documents. The study employs a mixed-methods approach, combining quantitative methods such as surveys and statistical analysis with qualitative methods including observations and interviews. This comprehensive approach allows for the development and assessment of the chatbot system within the context of SIM applications. The findings reveal that the chatbot significantly reduces processing time, improves user satisfaction, and streamlines the overall application experience. This integration demonstrates substantial potential for advancing public service delivery by making it more accessible and efficient. The research underscores that chatbot technology can play a crucial role in modernizing and optimizing public services, offering scalable solutions for future improvements in service delivery.